First Report and Morphological Study of Paraplagusia bilineata (Bloch, 1787) in the Arabian Sea, Gujarat, Northwest Coast of India - , Ritesh V. Borichangar; , Jeet N. Parmar; , Sheetal K. Bharda; , Bhavika R. Tandel; , Lata V. Tandel; , Upasana D. Vyas (Archives of Current Research International, 2025)
The present study reports an additional record of the rare flatfish, Double lined tongue sole Paraplagusia bilineata (Cyanoglossidae), off Dholai fishing harbour, Gujarat, India. One specimen was caught in a trawl net at a depth of 30–32 m around the coast of Gujarat. The total length and weight of the specimen were recorded as 20.4 cm and 60.5 g, respectively. In total, 18 morphometric parameters were closely observed and recorded for the taxonomic identification and confirmation of the species using morphometric analysis with traditional morphometrics. Paraplagusia bilineata is categorized as ‘Least Concern’ in the IUCN Red List, with the latest assessment conducted in 2021. Previously, P. bilineata was not reported in Gujarat. This study serves as the initial report of the presence of Paraplagusia bilineata from Dholai fishing harbour, Gujarat, on the Northwest coast of India.